GASTRONOMIC ANALYSIS OF TRADITIONAL CHOI PAN AS A TOURISM ATTRACTION IN SINGKAWANG CITY – WEST BORNEO - Qomara Lamasyilala; Lastiani Warih Wulandari; Pipin Kusumawati (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Choi Pan is a traditional dish originating from Singkawang City, West Kalimantan. This study aimed to analyze the gastronomic components of traditional Choi Pan food as a gastronomic tourism attraction in Singkawang City, West Kalimantan. This research adopted a qualitative methodology using observation, interviews, and documentation to determine many aspects of gastronomy. The results of the study showed that Choi Pan has significant allure due to its rich heritage and the innovative used of ingredients like as jicama, chives, taro, bamboo shoots, and young papaya, which provided a tender, chewy texture and a savory-sweet flavor. The unique consuming experience was enhanced by an addition of chili sauce and garlic oil, which intensify the sensory experience and strengthen the connection between entrepreneurs and Choi Pan lovers.   The nutritional benefits of Choi Pan contributed to the survival of this dish within a healthy local culture. The results indicated that the success of establishing Choi Pan as a culinary tourist destination depended not just on its flavor and texture, but also on its sustainability of its fundamental philosophy and culture. Consequently, enhancing gastronomy qualities was anticipated to augment the appealing factor of gastronomic tourism, facilitated cultural preservation and regional economic growth via the promotion of culture-centric gastronomic tourism.